2017
DOI: 10.1007/s00464-016-5410-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing for a second ERCP after failure of initial biliary cannulation following precut sphincterotomy: an analysis of experience at two tertiary centers

Abstract: A second ERCP after failure of initial biliary cannulation following precut appears to be safe and effective. A second ERCP should be delayed at least 4 days if feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…In 9 studies that analyzed the role of repeat attempt at ERCP (▶ Table e5, available online), repeat ERCP was successful in 442 of 537 patients (82 %). Of note, the three studies that analyzed the timing of repeat ERCP found that ERCP was more frequently successful if it was repeated at least 2 days [129,131] or 4 days [127] after the first attempt. A suggested explanation includes better visualization of the opening of the bile duct because of decreased edema or disappearance of submucosal injection.…”
Section: Repeat Attempts At Ercpmentioning
confidence: 99%
“…In 9 studies that analyzed the role of repeat attempt at ERCP (▶ Table e5, available online), repeat ERCP was successful in 442 of 537 patients (82 %). Of note, the three studies that analyzed the timing of repeat ERCP found that ERCP was more frequently successful if it was repeated at least 2 days [129,131] or 4 days [127] after the first attempt. A suggested explanation includes better visualization of the opening of the bile duct because of decreased edema or disappearance of submucosal injection.…”
Section: Repeat Attempts At Ercpmentioning
confidence: 99%
“…Despite advances and new developments in endoscopic accessories such as endoscopic instruments, selective biliary cannulation fails in %5-15 of cases, even in expert, high-volume centers [11]. Repeating ERCP within a few days of the first failed pre-incision reduces the risk of complications by reducing the edema of the papilla and increases the chance of cannulation [12][13][14][15]. In our study, cannulation was performed with a sphincterotome in 563 (95.2%) of 591 patients without diverticula, 28 (90.3%) of 31 type I patients, 76 (88.3%) of 86 type II patients and 144 (92.3%) of 156 type III patients.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve maximum effectiveness, the endoscopist should consider the following steps after a failed cannulation attempt: (1) Describe the anatomy of the papilla and characterize it (floppy, flat, mobile, ob- scure, and swollen), ( 2) describe the mucosa overlying the channel and make an incision over the mucosa to expose the superior border of the bile duct, (3) describe the bile duct and perforate it until observing the bile stained flow, and (4) continue the procedure with standard sphincterotome and guidewire. [6] Swan et al [16] reported that, in cases of cannulation failure, referral to experienced, high-volume, tertiary centers resulted in a high success rate and a better outcome for patients. In the present study, 47 patients were referred from other hospitals following a failed ERCP, 46 of whom were cannulated successfully at the second attempt at our center.…”
Section: Figure 2 Severely Edematous and Swollen Papillamentioning
confidence: 99%
“…[3] Repeating ERCP within a few days after the initial unsuccessful precut is a successful strategy and should be attempted before contemplating more invasive, alternative interventions, such as percutaneous-endoscopic or endoscopic ultrasound-guided rendezvous procedure, percutaneous transhepatic, or surgical intervention. [4][5][6][7][8][9][10] However, there is still no consensus regarding the clinical outcomes of failed ERCP patients who underwent precut sphincterotomy. In the current work, we present the therapeutic approach and the outcomes of our patients with failed ERCP due to several reasons.…”
Section: Introductionmentioning
confidence: 99%